2011
DOI: 10.1111/j.1741-3729.2010.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement in Urban Low-Income Fathers: Baseline Associations and Changes Resulting From Preventive Intervention

Abstract: This study investigates father involvement among a sample of ethnically diverse, low‐income men participating in a randomized controlled trial of a 14‐hour relationship education program that teaches skills and principles for healthy relationships. Utilizing data from 137 fathers, we examined contextual, individual, and coparental relationship pretest correlates of father involvement and found the strongest predictors were income, religiosity, ethnicity, and parenting alliance. Pre‐post analyses on a subsample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 45 publications
3
62
0
7
Order By: Relevance
“…Many intervention programs have therefore been developed to promote paternal involvement and positive family outcomes (e.g., Cowan et al 2009;Panter-Brick et al 2014;Rienks et al 2011). Some of these programs focus specifically on the co-parenting relationship and are designed to reduce maternal gatekeeping and enhance collaboration between parents (McHale and Carter 2012; Pruett et al 2017).…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Many intervention programs have therefore been developed to promote paternal involvement and positive family outcomes (e.g., Cowan et al 2009;Panter-Brick et al 2014;Rienks et al 2011). Some of these programs focus specifically on the co-parenting relationship and are designed to reduce maternal gatekeeping and enhance collaboration between parents (McHale and Carter 2012; Pruett et al 2017).…”
Section: Practice Implicationsmentioning
confidence: 99%
“…In addiction, Barkley and colleagues (2000) found that parental education was a stronger predictor of parent participation than socioeconomic status or parental depression. More recent research had replicated most of these findings, particularly the positive relationship between parent's education level and attendance and the negative association between participation and family structure (singe-parent families), large number of children, low family income and larger family size (Quinn, Hall, Smith & Rabiner, 2010;Rienks, Wadsworth, Markman, Einhorn & Etter, 2011;Eisner & Meidert, 2011;Bloomquist at al., 2012). However, Eisner & Meidert, (2011) found that being a single parent was not linked to less parental participation.…”
Section: Demographic and Contextual Variablesmentioning
confidence: 87%
“…Las variables de relación coparental (a saber, estado civil, conflicto, cooperación) parecen estar estrechamente relacionadas con la participación parental. Una serie de estudios han indicado que un mayor grado de alianza parental en la crianza y unos niveles inferiores de comunicación negativa guardan una relación positiva con la implicación parental en los programas familiares (McBride y Rane, 1998; Rienks et al, 2011).…”
Section: Características De Crianza Y Participaciónunclassified
See 1 more Smart Citation
“…Our findings highlight the importance of parents' identities and stress the need to address the salience and centrality of parental identities as part of the intervention. For example, a recent short-term group intervention delivered co-parenting relationship workshops to increase fathers' participation (Rienks, Wadsworth, Markman, Einhorn, & Moran Etter, 2011). Such interventions can be further honed by addressing fathers' parental identities, including their accessibility and subjective importance to the self as well as their meanings.…”
Section: Practice Implicationsmentioning
confidence: 99%